Biochar and Tillage Systems Influenced on Soil Physical Properties - Darusman Darusman; Syahruddin Syahruddin; syakur syakur; Manfarizah Manfarizah (Graduate Program of Syiah Kuala University, 2017)
Biochar is known as a huge carbon storage in the soil. In the soil, biochar absorbs CO2 from air and keep them for hundred years. In addition to preventing reduce emission and green house effects, Biochar also contributes to soil productivity such as physical dan chemical properties of the soil. How biochar amends soil physical properties combined with some tillage systems are imperative to find out. Study aimed to determine the influence of biochar and tillage systems on some soil physical properties. Treatment arranged in a factorial randomized block design with three replications. The treatment of biochar effect consisting of four levels; 0, 10, 15, and 20 t ha-1 Biochar. The tillage systems were three levels; no, minimum, and conventional tillage. The results showed that we found an interaction effect on the biochar application with tillage systems on dried bulk density, soil porosity, and soil permeability. No interaction was found on aggregate stability indexes and soil water holding capacity at water content at -0.3 and -15 bar of water potential (pF 2.54 and 4.2, accordingly). Biochar amounting 10 t ha-1 combined with minimum tillage gave significant benefits on soil productivity in terms of dried bulk density, porosity and soil permeability.